Overexpression of β-Catenin Induces Cisplatin Resistance in Oral Squamous Cell Carcinoma. (27th July 2016) - Li, Long; Liu, Hai-Chao; Wang, Cheng; Liu, Xiqiang; Hu, Feng-Chun; Xie, Nan; Lü, Lanhai; Chen, Xiaohua; Huang, Hong-Zhang
Abstract : Abnormal expression of β -catenin contributes to tumor development, progression, and metastasis in various cancers. However, little is known about the relationship between abnormal expression of β -catenin and cisplatin chemotherapy in oral squamous cell carcinoma (OSCC). The present study aimed to investigate the effect of β -catenin on OSCC cisplatin resistance and evaluated the drug susceptibility of stable cell lines with β -catenin knockin and knockdown. In this study, we found that higher expression level of β -catenin can be observed in CDDP-treated cell lines as compared with the control group. Furthermore, the expression levels of β -catenin increased in both a concentration- and time-dependent manner with the cisplatin treatment. More importantly, the nuclear translocation of β -catenin could also be observed by confocal microscope analysis. Stable cell lines with CTNNB1 knockin and knockdown were established to further investigate the potential role and mechanism of β -catenin in the chemoresistance of OSCC in vitro and in vivo. Our findings indicated that overexpression of β -catenin promoted cisplatin resistance in OSCC in vitro and in vivo. We confirmed that GSK-3 β, C-myc, Bcl-2, P-gp, and MRP-1 were involved in β -catenin-mediated drug resistance. Our findings indicate that the Wnt/β -catenin signaling pathway may play important roles in cisplatin resistance in OSCC.